2009
DOI: 10.1073/pnas.0810956106
|View full text |Cite
|
Sign up to set email alerts
|

The role of PTEN/Akt/PI3K signaling in the maintenance and viability of prostate cancer stem-like cell populations

Abstract: Characterization of the molecular pathways that are required for the viability and maintenance of self-renewing tumor-initiating cells may ultimately lead to improved therapies for cancer. In this study, we show that a CD133 ؉ /CD44 ؉ population of cells enriched in prostate cancer progenitors (PCaPs) has tumor-initiating potential and that these progenitors can be expanded under nonadherent, serum-free, sphere-forming conditions. Cells grown under these conditions have increased in vitro clonogenic and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
460
4
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 508 publications
(513 citation statements)
references
References 30 publications
43
460
4
6
Order By: Relevance
“…The fact that CD90 þ cell populations reduce to only about 4% in CHGA07 monolayercultured cells as compared with 21.5% in xenografted CHGA07 tumors suggests that CSCs populations undergo differentiation and progression under in vitro culturing conditions, which leads to the loss of their CSCs properties. This interesting finding may possibly offer an explanation for why researchers were only able to identify rare CSC population in established cancer cell lines (Dubrovska et al, 2009;Fukuda et Trastuzumab targets the CSC population in gastric tumors J Jiang et al that our methods to establish primary tumor models might already allow the in vivo selection of aggressive and highly tumorigenic tumor subsets during tumor establishment. Thus, the CD90 þ population potentially could be lower in clinical samples.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The fact that CD90 þ cell populations reduce to only about 4% in CHGA07 monolayercultured cells as compared with 21.5% in xenografted CHGA07 tumors suggests that CSCs populations undergo differentiation and progression under in vitro culturing conditions, which leads to the loss of their CSCs properties. This interesting finding may possibly offer an explanation for why researchers were only able to identify rare CSC population in established cancer cell lines (Dubrovska et al, 2009;Fukuda et Trastuzumab targets the CSC population in gastric tumors J Jiang et al that our methods to establish primary tumor models might already allow the in vivo selection of aggressive and highly tumorigenic tumor subsets during tumor establishment. Thus, the CD90 þ population potentially could be lower in clinical samples.…”
Section: Discussionmentioning
confidence: 90%
“…Previously, it has been shown that neuro-sphere formation in vitro is useful for the isolation of neural stem cells (Reynolds and Weiss, 1992). Up to date, CSCs have been isolated from several types of tumors, including breast and prostate cancers, by similar approaches (Dontu et al, 2003;Dubrovska et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, activation of the PI3K/Akt signaling pathway is associated with enhanced PC cell proliferation, invasion, metastasis, chemo-/radio-resistance, stemness and EMT, which would indicate that PI3K-targeting modalities could be a promising method to eliminate CSCs and to overcome treatment-resistance of PC. [36][37][38] In this study, we identified Tpl2 as a master regulator that controls the EMT and stemness of CRPC. Although Tpl2 protein kinase does not directly phosphorylate PI3K, PI3K is a downstream component of FAK/Akt and CXCL12/CXCR4 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Survival of mice was significantly increased following Tpl2 KD [PC3-shTpl2, 84 (57-90) days; PC3-shCon, 34 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) days; Supporting Information Fig. 2a].…”
Section: Tpl2 Enhances In Vivo Tumorigenesis and Metastasis Of Adi Pcmentioning
confidence: 99%